Exploring Academic Reading Skills Challenges and Strategies from the Perspective of Indonesian IELTS Test-Takers - Indry Widyasti Anwar; Magvirah Octasary; Aulia Dwiyanti (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
Academic reading is an essential competency for EFL learners, especially for those preparing for the IELTS examination, although it continues to create significant challenges. This study examines the issues encountered by Indonesian IELTS candidates in the reading section and analyzes the tactics they utilize to overcome these obstacles. A mixed-method approach was employed to collect data via questionnaires and open-ended responses from 24 participants in an IELTS preparation program in Ternate City. Quantitative data were evaluated using SPSS, and qualitative data were thematically interpreted to enhance the findings. Findings indicate that restricted vocabulary, time limitations, and comprehension challenges are the primary barriers faced by examinees. Participants indicated adopting multiple strategies to tackle these challenges, with skimming, scanning, highlighting important information, and employing contextual hints being the most commonly adopted techniques. The results highlight the significance of strategic instruction and vocabulary enhancement in preparing students for IELTS reading assessments. This study indicates that focused instruction and regular practice can improve learners' reading efficiency and performance in high-stakes language assessments.